STRATEGI PERSIAPAN MASA PENSIUN BAGI PARA KARYAWAN - Paidi, - (E-Journal Widya Ekonomika, 2017)
Retirement is a time that naturally would have faced by every employee upon retirement ages limits. For some people. Retirement is regarded as an unpleasant period due to declining income and the loss of its own authority (post-power syndrome). But many people are not yet ready and understand how important it is to prepare earlier to face retirement. The purpose of this paper is to: (1) discuss retirement for employees, (2) the strategies how to prepare in facing retirement. The methods used are examination of the descriptive exploratory approach with library research. It can be concluded that: (1) the existence of the pessimistic assumption about retirement is entering an old age and as asign of someone's been useless and not needed anymore in the world of work because productivity has decreased and the loss of its own authority (post-power syndrome), (2) many employees in Indonesia are not ready mentally and financially to cope with retirement. (3) making the preparation earlier in facing the retirement by is required by each employee for having retirement life which can be calm, comfortable and prosperous phisically and mentally (4) the strategies in preparing retirement among other things: (a) preparing financial planning through the projected savings and investment, or (b) keep the networking (friendship), (c) maintain a healthy life patternsand conduct religious activities.